Análise da espessura da película de cimentos de ionômero vítreo e fosfato de zinco, empregados na cimentação de coroas totais metálicas, preparadas in vivo - Pavanelli, Carlos Augusto [UNESP] (1997)
This study evaluated the film thicknesses of two GIC cements (Vidrion C, SS WHITE, Brazil; Ketac Cem, ESPE, Germany) and one zinc phosphate cement (Lee Smith, TELEDYNE, USA), used for final cementation of complete metal crowns. Twenty-one teeth scheduled for extraction due to orthodontic treatment were prepared for complete metal crowns. Dies were relieved with 5 layers of die varnish spacer. The crowns were manufactured by a commercial laboratory (with standardized procedures as much as possible) and cemented first with finger pressure and later by occlusion pressure using orange wood sticks. Results submitted to an ANOVA test showed that all cements had a similar behavior showing no significant statistical differences (p<0.01). A film thickness analysis of 7 selected preparations sites, showed that only axial positions, presented differences between Lee Smith and Vidrion C cements, the latter presenting lower significant values. For other positions studied, the three cements showed no significant statistical differences (p<0.05). Technical exploratory analysis of data by a BOX PLOT graphic showed for the ZPC a broad film thickness value distributions (from the highest to the lowest values) related to type of cement and measurement values. For glass ionomer cement the graphic presented values concentrating at lower levels than zinc phosphate cement. This was still more evident for the Vidrion C cement